Chinese Storytelling in Domestic Animation Films from the Perspective of Cross-Cultural Communication——Take the Movie "Nezha" as an Example: 跨文化传播视角下国产动画电影的中国故事讲法——以电影《哪吒之魔童降世》为例 - Lu , Yuting (Mandarinable: Journal of Chinese Studies, 2000)
With the deepening of cultural exchanges between countries in the world today, how to tell the "Chinese story" well and establish cultural self-confidence has become an indispensable part of China's comprehensive approach to the world. As a kind of cultural product, the effects and ways of cross-cultural dissemination of film are widely concerned by academic circles. Therefore, this paper takes the film "Nezha's Devil Child Comes into the World" as an example, analyzes the film's cultural communication advantages and difficulties, and proposes four cross-cultural communication strategies for the problems existing in the process of cross-cultural communication.